A multimorbid condition involving uterine fibroid, ovarian cyst, fatty liver and contracted gall bladder managed with Homoeopathic dilutions: A case report - Pal, Partha Pratim; Nath, Madhumita (Indian Journal of Case Reports, 2025)
Uterine fibroid (UF) is a commonly occurring tumor in females, which is often associated with other medical conditions, leading to stress and reduced quality of life. The treatment options are limited to surgical removal of the tumor or other conventional therapy, which lacks a patient-centered approach. The homoeopathic system of medicine is based on the individualistic approach, and chronic diseases are well treated, covering all aspects of a patient. In this case, a female patient, aged 25 years, was treated for her complaints associated with UF, ovarian cyst, grade II fatty liver, and contracted gall bladder with Sepia officinalis LM potencies. Later, with stagnation of improvement in UF, the prescription of Aurum muriaticum natronatum in centesimal potencies eventually helped to diminish the uterine pathology and elevated the overall health satisfaction.